The Phrasemes with the Component RED in Russian and Macedonian (Slavic Studies, 2024)
The phenomenon of colors, their meaning and perception are the subject of interest of many researches from different fields. Тhis paper is an attempt to shed light on another segment of this complex phenomenon. In particular, the article focuses on the phrasemes with the colorative red in Russian and Macedonian languages, by identifying all the units containing this colorative and determining the differences related to their representation in the considered languages.